Serie "Unser Zeichen ist die Sonne", no. 8. Peters als Produktionsdirektor der Volkswerft Stralsund (1983)
Serie "Unser Zeichen ist die Sonne", no. 8. Peters als Produktionsdirektor der Volkswerft Stralsund.